Clinical phenotype and genetic characteristics of five patients with adrenomyeloneuropathy - LIU Xiao⁃li (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To report 5 patients with adrenomyeloneuropathy (AMN), and to summarize the clinical phenotype and gene mutation characteristics in combination with literature and mutation database. Methods and Results Five patients with AMN who were treated in the Department of Neurology, Shanghai Sixth People's Hospital Affiliated to Shanghai Jiaotong University and Shanghai Fengxian District Central Hospital from May 2008 to December 2021 were selected. Spastic paraplegia was the main manifestation in all the 5 patients. Laboratory test showed that Case 2 had abnormal levels of very long⁃chain fatty acids (VLCFA), and Case 5 had higher level of adrenocorticotropic hormone (ACTH). Cranial MRI showed multiple ischemic foci in the right frontal parietal lobe, brainstem and cerebellum in Case 5. Three patients (Case 2, Case 3, Case 5) underwent spinal MRI and showed protrusion of intervertebral disc or degenerative change of vertebral body. Gene detection showed that all 5 patients had pathogenic mutation located in exon 1 of ABCD1 gene, Case 1 was c.421G＞A (p.Ala141Thr) hemizygous mutation, Case 2 was c.454C＞G (p.Arg152Gly) hemizygous mutation, Case 3 was c.521A＞G (p.Tyr174Cys) hemizygous mutation, Case 4 and Case 5 from the same family, all of them were c.293C＞T (p.Ser98Leu) hemizygous mutation, which were "pathogenic" mutations, and the c.454C＞G mutation was first reported in this study. This study summarized the genetic variation of ABCD1 gene in the adrenoleukodystrophy (ALD) mutation database. The ALD mutation database contained 1255 genetic variations, which were distributed in exons, introns and 5' untranslated region (5'UTR) regions, of which exon 1 (43.12%, 370/858) and exon 6 (10.02%, 86/858) were the most common. Conclusions The diagnosis of ALD with spastic paraplegia as its main manifestation needs to be combined with clinical manifestations and imaging examinations. ABCD1 gene detection is important for diagnosis. Exon 1 and 6 are hotspot exons of ABCD1 gene.